Can we find the perfect oil to protect the perineum? A randomized-controlled double-blind trial. (16th April 2013) - Harlev, Avi; Pariente, Gali; Kessous, Roy; Aricha-Tamir, Barak; Weintraub, Adi Y.; Eshkoli, Tamar; Dukler, Doron; Ayun, Saviona Ben; Sheiner, Eyal
Abstract: Objective : To determine whether perineal massage during the second stage of labor using oil enriched with vitamins, increases the chances of delivering with an intact perineum as compared to perineal massage using pure liquid wax. Method : A prospective, randomized, double-blind study was conducted. Women were assigned to liquid wax (jojoba oil) versus purified formula of almond and olive oil, enriched with vitamin B1, B2, B6, E and fatty acids. The caregivers used the oils during the second stage of labor. Results : A total of 164 women undergoing vaginal delivery were recruited. No significant differences regarding perineal lacerations, number of sutures and length of suturing were noted between the two groups. Likewise, while analyzing separately nulliparous and multiparous women, no significant differences were noted. Controlling for birth weight >4000 g, using the Mantel–Haenszel technique, no association was noted between perineal lacerations and the type of oil used (weighted OR = 0.9, 95% CI 0.3–2.4; p  = 0.818). Conclusion : The type of the oil used during the second stage of labor for prevention of perineal tears has no effect on the integrity of the perineum. Accordingly, it seems that there is no perfect oil.